COMPARISON OF THE METHODS OF PENETRATION OF THE ENEMY'S AIR ATTACK MEANS IN REINFORCED CONCRETE STRUCTURES OF CRITICAL INFRASTRUCTURE FACILITIES PROTECTION (Collection of scientific works «Modern structures of metal and wood», 2024)
On  the  basis  of  the  literature  review,  trends  in  the  development  of  studies  of engineering protection of critical infrastructure objects were revealed. The review of scientific works revealed the direction of improving the physical and mechanical properties of building protective structures.  It  is  noted  that  large-scale  experimental  and  theoretical  studies  of  reinforced  concrete structures  and  reinforced  concrete  protective  plates  with  the  use  of  fiber  were  carried  out. Experimental and theoretical studies of reinforced concrete protective structures on the impact of rockets and the subsequent explosion have been identified and summarized. The study of structures using different materials is shown. It was determined that one of the promising directions is the use of  multilayer  composite  structures.  The  results  of  experimental  studies  by  various  authors  were analyzed and it was concluded that air damage impacts should be classified into 4 categories: an impact, a soft impact, a hard impact of a projectile with a steel shell; a semi-solid impact is the impact of a missile whose outer shell is made of a composite material or a thin-walled titanium alloy. The authors  also  draw  attention  to  the  possibility  of  studying  an  all-plastic  impact  -  the  impact  of  a concrete-piercing warhead of a missile with a 20-22 mm titanium body, the impact is accompanied by  the  development  of  plastic  deformations  in  the  shell  during  penetration  into  the  composite reinforced concrete layer. An overview of the main methods of calculating the penetration of combat units during an impact on defensive structures was carried out. The formulas of the main methods are based on the results of experimental and theoretical studies NDRC. Effects of impact and explosion. Summary Technical Report Division 2, 1, National Defense Research Committee, Washington, DC, 1946". A generalized conclusion is made regarding the use of the modified NDRC (USA) method for evaluating experimental studies.